A new species of Demidospermus (Platyhelminthes, Monogenea, Ancyrocephalidae) from the catfish Parapimelodus valenciennis in Samborombón Bay, Argentina - Marcotegui, Paula Soledad (2011)
Demidospermus annulus sp. nov. (Platyhelminthes, Monogenea, Ancyrocephalidae) is described from the gills of the catfish Parapimelodus valenciennis Lütken collected in Samborombón Bay, Argentina. The new species differs from all congeneric species mainly by the structure of the accessory piece of the male copulatory organ, the sclerotized ring-shaped vaginal aperture and the dorsal bar articulation.